Molecular mechanisms of cocaine reward: Combined dopamine and serotonin transporter knockouts eliminate cocaine place preference - Sora, Ichiro (The National Academy of Sciences, 2001)
Cocaine blocks uptake by neuronal plasma membrane transporters for dopamine (DAT), serotonin (SERT), and norepinephrine (NET). Cocaine reward/reinforcement has been linked to actions at DAT or to blockade of SERT. However, knockouts of neither DAT, SERT, or NET reduce cocaine reward/reinforcement, leaving substantial uncertainty about cocaine's molecular mechanisms for reward. Conceivably, the molecular bases of cocaine reward might display sufficient redundancy that either DAT or SERT might be able to mediate cocaine reward in the other's absence. To test this hypothesis, we examined double knockout mice with deletions of one or both copies of both the DAT and SERT genes. These mice display viability, weight gain, histologic features, neurochemical parameters, and baseline behavioral features that allow tests of cocaine influences. Mice with even a single wild-type DAT gene copy and no SERT copies retain cocaine reward/reinforcement, as measured by conditioned place-preference testing. However, mice with no DAT and either no or one SERT gene copy display no preference for places where they have previously received cocaine. The serotonin dependence of cocaine reward in DAT knockout mice is thus confirmed by the elimination of cocaine place preference in DAT/SERT double knockout mice. These results provide insights into the brain molecular targets necessary for cocaine reward in knockout mice that develop in their absence and suggest novel strategies for anticocaine medication development.